A mulher na poesia de cordel de Leandro Gomes de Barros - Mendes, Sandileuza Pereira da Silva (2009)
Studies the presence of the feminine behavior in the twine poetry of Leandro Gomes de Barros, from the brazilian cultural revalorizes in its multiple looks, which if they had reflected, in the diverse scientific, educational and social fields. For in such a way, it establishes the boarding of literary and social analysis from the perception of the feminine universe in the twine. It points out the sprouting of the twine literature, with the focus directed to its characteristics and formal structure. Feminist verifies the epistemological analysis – that she confers practical the feminine behavior as contributing in cultural the popular author twine, the source of the woman participant author and not personage of the twine. From this context, concernment‘s questions to the resistance of the twine literature will be displayed until the contemporary, and the relation of the author twine with the presence of the constituent woman while and/or to be constituted. They will not leave of being boarded: the analysis of the feminine image printed in twines, from the technique and aesthetic xylographical; the presentation of biographical peculiarities of Leandro Gomes de Barros and analysis of the feminine behavior in infancy, adolescence, maturity and oldness. Also relative attributions to the relation will be made man/woman, characterized for the seduction and feminine devoir of the twine literature using itself of concepts of being able constituent, common singularity and.